The outlook for natural gas demand in Europe - Anouk Honoré (The Oxford Institute for Energy Studies, 2014)
A report published by the Natural Gas Programme of the Oxford Institute for Energy Studies, concludes that European gas demand will not recover its 2010 level until about 2025. Dr Anouk Honoré has produced the most comprehensive independent study of European gas demand by country and by sector available in the public domain. The scenarios show that natural gas demand in the 35 countries of the European region falls from 594 Bcm in 2010 to 564 Bcm in 2020 and then rises to 618 Bcm in 2030. Only 24 Bcm in two decades may seem very pessimistic, but one must not forget the sharp decline that already happened in 2010-2013. Focusing on the 2013-2030 period, then 88 Bcm of additional gas consumed is expected. Even before the financial crisis of 2008 and subsequent financial recession, European demand growth had slowed, however a product of both a maturing market, low population growth, higher gas prices (in large part due to the oil price linkage in much of its contracted imports) and the migration of manufacturing industry to other world regions. Assessing the long term prospects for European gas demand against this backdrop would be challenge enough. The additional dimensions of EU renewables and decarbonisation policy, the Large Combustion Plant Directive, the Industrial Emissions Directive, the German Energiewende and other country-specific policies and diverse national power generation mix `starting points' take the challenge into `formidable' territory, especially in the current uncertain post-economic crisis landscape. This paper addresses all the major `known unknowns' as far as this is possible and proposes an overview of the gas demand fundamentals in Europe to 2020 and 2030 horizons. Readers will find in the appendix all the key assumptions set out in detail at a national level which, when aggregated, form the basis for the demand outlook scenario.
Keywords: 330; Erdgas; Nachfrage; Prognose; Europa